2013
DOI: 10.1016/j.pain.2013.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Nocebo hyperalgesia induced by social observational learning

Abstract: Nocebo effects can be acquired by verbal suggestion, but it is unknown whether they can be induced through observational learning and whether they are influenced by factors known to influence pain perception, such as pain anxiety or pain catastrophizing. Eighty-five female students (aged 22.5 ± 4.4 years) were randomly assigned to one of three conditions. Participants in the control condition (CC) received information that an ointment had no effect on pain perception. Participants in the verbal suggestion cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(184 citation statements)
references
References 65 publications
9
170
1
4
Order By: Relevance
“…Previous research has generally not made such distinctions-either grouping all symptoms together or examining only modeled symptoms and often not considering the role of attribution. The results with regard to specific symptoms are in line with previous research which indicates that social modeling results in increased nocebo effects soon after the social modeling procedure [13,14,16,17]. Similar to results reported by Mazzoni et al [18], female participants seated with a female model reported symptoms at significantly higher rates, regardless of social modeling condition.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous research has generally not made such distinctions-either grouping all symptoms together or examining only modeled symptoms and often not considering the role of attribution. The results with regard to specific symptoms are in line with previous research which indicates that social modeling results in increased nocebo effects soon after the social modeling procedure [13,14,16,17]. Similar to results reported by Mazzoni et al [18], female participants seated with a female model reported symptoms at significantly higher rates, regardless of social modeling condition.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous social modeling literature [13,14], participant empathy was assessed using the IRI [31]. This scale comprises four subscales of seven items each, with a total of 28 items.…”
Section: Empathymentioning
confidence: 99%
See 2 more Smart Citations
“…Observational learning such as watching and/or listening to others who report serious problems after taking a specific drug is another powerful tool for symptom development, sometimes even more powerful than the mere verbal suggestion of side effects (Vögtle et al, 2013). The social dissemination of somatic symptoms was demonstrated elegantly in a recent study .…”
Section: B Psychologic Mechanisms Contributing To Nocebo Responsesmentioning
confidence: 99%